Implementing Differentiated Learning to Enhance Mathematical Reasoning Readiness for University Entrance Assessment: A Classroom Action Research in Madrasah Aliyah - Rizvi Uzza Awwawina; Budi Waluya; Iqbal Kharisudin (Research Journal on Teacher Professional Development, 2026)
This classroom action research aims to test the implementation of differentiated learning in improving the readiness of grade XII students to face the mathematical reasoning component in the Computer-Based Written Examination (UTBK), especially in madrasah schools. The study used a classroom action research design according to Arikunto et al. which was carried out through two cycles that included planning, implementation, observation, and reflection. The research subjects consisted of 34 grade XII science students at MA Sunan Prawoto Pati in the even semester of the 2025/2026 academic year. Differentiated learning was implemented through adjusting content, processes, and products based on students' readiness levels (high, medium, and low). Data were collected through learning outcome tests, observation sheets, and student perception questionnaires, then analyzed descriptively. The results showed a consistent increase in all indicators. The average student score increased from 58.4 at the initial condition to 69.2 in Cycle I and 81.5 in Cycle II, while learning completeness increased from 35.3% to 61.7% and finally reached 88.2%. Teachers' implementation of the learning model increased from 82% to 94%, while 85% of students reported that learning tailored to their level of readiness made them more comfortable and confident in solving mathematical reasoning problems. These findings suggest that differentiated learning improves academic achievement while strengthening learning engagement and reasoning skills by aligning learning strategies with students' learning needs. This study contributes by providing empirical evidence that differentiated learning within a classroom action research framework is an effective strategy for preparing students for reasoning-based mathematics assessments such as the Computer-Based Test (UTBK) and offers an adaptive learning model that can be applied to classes with heterogeneous student abilities